CLINICAL AND PARACLINICAL CHARACTERISTICS OF PREGNANT WOMEN UNDERGOING PROPHYLACTIC CERVICAL CERCLAGE TO PREVENT MISCARRIAGE AND PREMATURE BIRTH AT ANDROLOGY AND FERTILITY HOSPITAL OF HANOI (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical and paraclinical characteristics of pregnant women undergoing prophylactic cervical cerclage to prevent miscarriage and preterm birth at Andrology and Fertility Hospital of Hanoi from January 2024 to December 2024.Subject and methods: A cross-sectional study was conducted on 105 pregnant women who underwent prophylactic cervical cerclage at Andrology and Fertility Hospital of Hanoi from January 2024 to December 2024. Data on general characteristics, obstetric history, clinical features, and paraclinical characteristics were collected and analyzed.Results: The mean age of participants was 31.51 ± 4.96 years (range 22-45 years). Among them, 55.2% had a history of miscarriage before 22 weeks, and 64.8% had a history of one previous preterm birth. Cesarean delivery history was 14.3% of cases, and 29.5% had a previous history of cervical cerclage. Regarding conception methods, 51.4% conceived via in vitro fertilization, 44.8% conceived naturally, and 3.8% via intrauterine insemination. Most women had a closed cervix at the time of cerclage placement (98.1%). The mean gestational age at the time of cerclage was 13.72 ± 1.29 weeks (range 12-16 weeks). Uterine abnormalities were 3.8% (4/105 pregnant women) of participants. The mean cervical length on pre-cerclage transvaginal ultrasound was 31.30 ± 4.64 mm (range 16.8-45.2 mm), with 94.3% having a cervical length over 25 mm.Conclusion: Women undergoing prophylactic cervical cerclage had a history of miscarriage or preterm birth. The procedure was performed mainly between 12 and 16 weeks of gestation, when the cervix remained closed and cervical length exceeded 25 mm. These findings provide the timing and indications for prophylactic cerclage in clinical practice.
Keywords: Cervical cerclage, miscarriage prevention, preterm birth, clinical, paraclinical characteristics.